The Development of Health Tourism in Ornamental Plant Village Khlong 15, Ongkharak District, Nakhon Nayak Province - Chaiyasung, Phatcharaphan; Kaewdang, Pim-on; Sridet, Rutshaporn; Wong-oui, Warangkana (Journal of The Royal Thai Army Nurses, 2023)
This research and development aim to develop health tourism in Ornamental plant village Khlong 15, Nakhon Nayok Province. The sample group is including community leaders, public health volunteers, and business owners who have shops in Khlong 15 and are interested in managing health tourism sites total 50 participants. Purposive sampling was used to select the sample according to the criteria. The research tools for data collection were 1) The questionnaire is divided into 3 parts were, Part 1: a health tourism knowledge test, Part 2: a skill assessment form for organizing activities to be a tourist attraction, Part 2: a questionnaire for the satisfaction of community leaders in participating in the activities, 2) an in-depth interview form management of health tourism, 3) a program for developing community leaders’ potential in organizing a health tourism. Quantitative data analysis using percentage, mean, standard deviation statistics, and paired t-test by setting the significance level at 0.5. Qualitative data were analyzed by the content analysis method. The research tools were 1) a program for developing community leaders’ potential in organizing a health tourism, 2) a health tourism knowledge test, 3) a skill assessment form for organizing activities to be a tourist attraction, 4) a questionnaire for the satisfaction of community leaders in participating in the activities, and 5) an in-depth interview form management of health tourism. Quantitative data analysis using percentage, mean, standard deviation statistics, and paired t-test by setting the significance level at 0.5. Qualitative data were analyzed by the content analysis method. The research results were found: 1) The health tourism model in Ornamental plant village Khlong 15 has activities to produce healthy drinks, herbal water, and a herb plant, but it is not yet clearly categorized into a model, and 2) There is prototype one health tourism route, which is a one-day round-trip boat tour with health promotion activities. In addition, 3) after engagement in the program of developed community leaders’ potential in organizing health tourism sites, the sample group had knowledge and skills in organizing activities for a health tourism attraction statistically significantly higher than before (p<.05). Furthermore, the overall satisfaction of the participants in the project was at a high level (Mean = 4.07, SD = 0.702). Suggestion: Development should choose a community-based management model so that the community can develop activities that are appropriate to the community’s context, To achieve sustainable development at the community level.